2016
DOI: 10.1016/j.bmc.2016.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Donor substrate promiscuity of bacterial β1–3-N-acetylglucosaminyltransferases and acceptor substrate flexibility of β1–4-galactosyltransferases

Abstract: β1–3-N-Acetylglucosaminyltransferases (β3GlcNAcTs) and β1–4-galactosyltransferases (β4GalTs) have been broadly used in enzymatic synthesis of N-acetyllactosamine (LacNAc)-containing oligosaccharides and glycoconjugates including poly-LacNAc, and lacto-N-neotetraose (LNnT) found in the milk of human and other mammals. In order to explore oligosaccharides and derivatives that can be synthesized by the combination of β3GlcNAcTs and β4GalTs, donor substrate specificity studies of two bacterial β3GlcNAcTs from Heli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 56 publications
4
50
0
Order By: Relevance
“…Formation of trisaccharyl sphingosine Lc 3 βSph (GlcNAcβ3Galβ4GlcβSph, 4 ) from LacβSph ( 5 ) was achieved by a one-pot four-enzyme N-acetylglucosamine (GlcNAc) activation and transfer system containing Bifidobacterium longum (strain ATCC55813) N -acetylhexosamine-1-kinase (BLNahK), 46 Pasteurella multocida N -acetylglucosamine uridylyltransferase (PmGlmU), 47 Pasteurella multocida inorganic pyrophosphatase (PmPpA), 48 and Neisseria meningitidis β1–3- N -acetylglucosaminyltransferase (NmLgtA) 49 in Tris-HCl buffer (100 mM, pH 8.0) at 37 °C for 52 hours. The BLNahK, PmGlmU, and PmPpA allowed in situ formation of uridine 5′-diphosphate- N -acetylglucosamine (UDP-GlcNAc), the sugar nucleotide donor substrate, efficiently and directly from monosaccharide GlcNAc for NmLgtA-catalyze formation of Lc 3 βSph ( 4 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Formation of trisaccharyl sphingosine Lc 3 βSph (GlcNAcβ3Galβ4GlcβSph, 4 ) from LacβSph ( 5 ) was achieved by a one-pot four-enzyme N-acetylglucosamine (GlcNAc) activation and transfer system containing Bifidobacterium longum (strain ATCC55813) N -acetylhexosamine-1-kinase (BLNahK), 46 Pasteurella multocida N -acetylglucosamine uridylyltransferase (PmGlmU), 47 Pasteurella multocida inorganic pyrophosphatase (PmPpA), 48 and Neisseria meningitidis β1–3- N -acetylglucosaminyltransferase (NmLgtA) 49 in Tris-HCl buffer (100 mM, pH 8.0) at 37 °C for 52 hours. The BLNahK, PmGlmU, and PmPpA allowed in situ formation of uridine 5′-diphosphate- N -acetylglucosamine (UDP-GlcNAc), the sugar nucleotide donor substrate, efficiently and directly from monosaccharide GlcNAc for NmLgtA-catalyze formation of Lc 3 βSph ( 4 ).…”
mentioning
confidence: 99%
“…The obtained Lc 3 βSph ( 4 ) was used for synthesizing nLc 4 βSph ( 3 ) using an improved OPME galactose (Gal) activation and transfer system 50 containing Streptococcus pneumoniae TIGR4 galactokinase (SpGalK), 51 Bifidobacterium longum UDP-sugar pyrophosphorylase (BLUSP), 50 PmPpA, and Neisseria meningitidis β1–4-galactosyltransferase (NmLgtB) 48, 49 in Tris-HCl buffer (100 mM, pH 8.0) at 37 °C for 30 hours. The SpGalK, BLUSP, and PmPpA allowed in situ formation of uridine 5′-diphosphate-galactose (UDP-Gal), the donor substrate of NmLgtB, from monosaccharide galactose (Gal) for the formation of LNnTβSph ( 3 ).…”
mentioning
confidence: 99%
“…Instead of carrying out α2–6-sialylation to introduce two α2–6-linked Neu5Ac simultaneously after the formation of LNnT using a β1–4-galactosyltransferase-catalyzed one-pot multienzyme (OPME) reaction, the formation of α2–3- and α2–6-linked Neu5Ac in DS′LNnT ( 5 ) was accomplished by α2–6-sialylation of the trisaccharide core GlcNAcβ1–3Galβ1–4Glc (Lc 3 , 10 ) followed by sequential extension of the core with β1–4-galactosylation and α2–3-sialylation. 17 As shown in Scheme 3, trisaccharide GlcNAcβ1–3Galβ1–4Glc (Lc 3 , 10 ) obtained from lactose in a one-pot four-enzyme GlcNAc-activation and transfer reaction 12 containing recombinant enzymes Bifidobacterium longum strain ATCC55813 N -acetylhexosamine-1-kinase (BLNahK), 18 Pasteurella multocida N -acetylglucosamine uridylyltransferase (PmGlmU), 19 Pasteurella multocida inorganic pyrophosphatase (PmPpA), 20 and Neisseria meningitidis β1–3- N -acetylglucosaminyltransferase (NmLgtA) 21 was used for α2–6-sialylation by the OP2E system containing NmCSS and Pd2,6ST. Tetrasaccharide GlcNAcβ1–3(Neu5Acα2–6)Galβ1–4Glc ( 11 ) (0.3 g) was obtained in an excellent 96% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Lac, Gal, and GalNAc were purchased from Fisher Scientific, Neu5Ac was from Atomole Scientific, UTP and CTP were from Chemfun Medical Technology Co., and ATP was from Beta Pharm Inc. Lacto- N -tetraose (LNT) was from Elicityl (Crolles, France). Recombinant enzymes Bifidobacterium longum strain ATCC55813 N -acetylhexosamine-1-kinase (BLNahK), 18 Pasteurella multocida N -acetylglucosamine uridyltransferase (PmGlmU), 19 Pasteurella multocida inorganic pyrophosphatase (PmPpA), 20 Neisseria meningitidis β1–3- N –acetylglucosaminyltransferase (NmLgtA), 21 Escherichia coli galactokinase (EcGalK), 22 Bifidobacterium longum UDP-sugar pyrophosphorylase (BLUSP), 23 Neisseria meningitidis β1–4-galactosyltransferase (NmLgtB), 20 Neisseria meningitidis CMP-sialic acid synthetase (NmCSS), 13 Photobacterium damselae α2–6-sialyltransferase (Pd2,6ST), 14 Pasteurella multocida α2–3-sialyltransferase 1 M144D mutant (PmST1 M144D), 24 Bifidobacterium infantis D-galactosyl-β1,3- N -acetyl-D-hexosamine phosphorylase (BiGalHexNAcP), 26 and Campylobacter jejuni β1–3-galactosyltransferase (CjCgtB) 33 were expressed and purified as described previously. HMOs used were obtained previously.…”
Section: Methodsmentioning
confidence: 99%
“…These substrates were exposed to the microbial fucosyl transferase Hp39-FT in the presence of GDP-fucose, and the conversion to the corresponding Lewis X( Le x )containing oligosaccharides 23-27 was monitored by capillary electrophoresis-mass spectrometry (CE-MS). [8] It was found that LacNAc 17 and LacNHTFA 18 were readily converted into the Le x -containing products 23 and 24.O nt he other hand, the presence of the Cbz-and Bsmoc-protecting groups of 19 and 20, respectively,c onsiderably slowed down the fucosylation and only partial product formation was observed. Strikingly,n oc onversion to Le x was observed for LacNH-Boc 21 and LacNH 2 22.S imilar results were obtained when FUT5 was employed.…”
Section: Introductionmentioning
confidence: 98%